PHYSICAL CULTURE AND ITS ROLE IN TRAINING THE STUDENTS OF NON-SPORTS HIGHER EDUCATIONAL INSTITUTIONS - Sergey V. Kaznacheyev; Irina B. Strakhova; Olga V. Lopatina (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to show long-felt need of formation of proof motivation to physical culture and skills of a healthy way of life among university students, whose specialties are not connected with the sports. Methods. The methods involve survey and questionnaire as a part of sociological research (such methods were used to find out what place occupies health in the system of modern students' values, and what are be the basic motives of a healthy way of life of student's youth). The standard computer statistical analysis was applied to processing of research results. Scientific novelty and results. Modern interpretation of the term «physical training» is given. Authors of the present study maintain and prove the fact that not only simply applied aspect of the formation, helping to achieve quality health of the person and to get the competence of professional sports, but also a science concerning the ways and technologies of achievement of harmony of the personal development, provide successful preparation for work on the chosen specialty. Data of sociological research shows stereotypic representations of students on physical training as a way of improvement of muscles work and increase its weight. The research show total imperception of the fact that muscles activity is reflected in emotionally-shaped thinking; successful mastering of modern scientific knowledge, active ability to live, successful implementation of personal and professional plans are impossible without such activities. Low valeological competence of parents, school teachers, tutors and teachers of higher schools is revealed as the main reason of an absence of students' organisation skills of a healthy way of life, and upkeeping the state of health. Practical significance. Research materials justify that the system of mass physical training requires conceptual reforming; it is required to include reconsideration of a place and role of the so-named discipline in the higher school.